2014
DOI: 10.4236/ojped.2014.41003
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in Fetal Alcohol Spectrum Disorders

Abstract: Objective: Mortality in FASD has not been well studied. In this paper we review published reports of mortality in FASD. Method: We searched using Pub Med for all years in all languages for reports of all-cause mortality associated with any FASD. Results: We located 26 papers reporting on 57 deaths. Cause of death was reported for 49/57 cases (86%). The two most prevalent potential causes of death were malformations of the heart (37 of 49 cases, 75.5%) which varied from atrial septal defect or patent ductus art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Thus, several hundred thousand pregnancies have PAE exposure at levels increasing risk for FASD. Whilst PAE can result in damage to any of the organ systems, the heart and brain appear to be the two most commonly reported organ systems [20]. However, recently Patel et al have reported that they found no increase in risk for non-syndromic atrioventricular septal defects attributable to maternal alcohol consumption in a large data set from the National Birth Defects Prevention Study [22].…”
Section: Mortality and Fetal Alcohol Spectrum Disordermentioning
confidence: 93%
See 4 more Smart Citations
“…Thus, several hundred thousand pregnancies have PAE exposure at levels increasing risk for FASD. Whilst PAE can result in damage to any of the organ systems, the heart and brain appear to be the two most commonly reported organ systems [20]. However, recently Patel et al have reported that they found no increase in risk for non-syndromic atrioventricular septal defects attributable to maternal alcohol consumption in a large data set from the National Birth Defects Prevention Study [22].…”
Section: Mortality and Fetal Alcohol Spectrum Disordermentioning
confidence: 93%
“…Case study reviews undertaken by Thompson et al relating to FASD and mortality indicate that there is an early age of death distribution which they found surprising given that a diagnosis of FASD is difficult in infancy and early childhood [20]. In fact, a diagnosis of FASD is often delayed until middle childhood and mortality rates in FASD are increased [23].…”
Section: Mortality and Fetal Alcohol Spectrum Disordermentioning
confidence: 99%
See 3 more Smart Citations